Incomplete conquests the limits of Spanish empire in the seventeenth-century Philippines - Mawson, Stephanie Joy (Ithaca Southeast Asia Program Publications, an imprint of Cornell University Press, 2023)
"This book tells a story of the limitations of empire, unearthing histories of resistance, flight, evasion, conflict, and warfare from across the breadth of the Philippine archipelago during the seventeenth century."
A Moment of Crisis: 1660-1663 -- Slavery, Debt, and Colonial Labor Regimes -- Contested Conversions -- Slave Raiding and Imperial Retreat -- Mountain Refuges -- Cagayan Insurgencies, 1572-1745 -- Manila: The Chinese City.
Includes bibliographical references and index.
Keywords: Indigenous peoples -- Philippines; Philippines -- History -- 1521-1812.; Philippines -- Colonization -- History -- 17th century; Spain -- Colonies -- Asia -- History -- 17th century